Sierra Gorda Biosphere Reserve, Querétaro, Mexico: An Example of Sustainable Tourism - HUERTA-MENDOZA, Ana-Karen; FISCHER, Laura (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).15, 2021)
The importance of tourism in the economy and development, from countries worldwide and specifically to Mexico, makes it increasingly necessary to carry out tourism activities and create sustainable policies that reduce the impacts of the mass movement of tourists. The work aims to present the different actions carried out in the Sierra Gorda Biosphere Reserve, Querétaro, Mexico that allow it to offer ecotourism activities and develop sustainable projects, which benefit the surrounding communities and allows the tourist a low impact approach with nature. Promoting a sustainable entrepreneurship model by consolidating economic development with biodiversity conservation.